2020
DOI: 10.1002/jmv.25798
|View full text |Cite
|
Sign up to set email alerts
|

Novel coronavirus treatment with ribavirin: Groundwork for an evaluation concerning COVID‐19

Abstract: Confronting the challenge of the outbreak of COVID-19 should sharpen our focus on global drug access as a key issue in antiviral therapy testing. The testing and adoption of effective therapies for novel coronaviruses are hampered by the challenge of conducting controlled studies during a state of emergency. The access to direct antiviral drugs, such as ribavirin, that have an existing inventory and reliable supply chain may be a priority consideration for therapies developed for the 2019-nCoV infection outbre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
226
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(242 citation statements)
references
References 45 publications
(61 reference statements)
0
226
0
9
Order By: Relevance
“…The effectiveness of antiviral treatment for COVID-19 is still controversial. Many researchers consider that ribavirin, remdesivir, lopinavir, emetine, and homoharringtonine have shown e cacy to inhibit SARS-CoV-2 or other coronavirus replication in vitro and combinational therapy may help to reduce the effective concentration of SARS-CoV-2 [13][14][15][16]. The molecular docking study has shown that the effectiveness of ribavirin, remdesivir, sofosbuvir, galidesivir and tenofovir as potent drugs for treating SARS-CoV-2 infection [17].…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of antiviral treatment for COVID-19 is still controversial. Many researchers consider that ribavirin, remdesivir, lopinavir, emetine, and homoharringtonine have shown e cacy to inhibit SARS-CoV-2 or other coronavirus replication in vitro and combinational therapy may help to reduce the effective concentration of SARS-CoV-2 [13][14][15][16]. The molecular docking study has shown that the effectiveness of ribavirin, remdesivir, sofosbuvir, galidesivir and tenofovir as potent drugs for treating SARS-CoV-2 infection [17].…”
Section: Discussionmentioning
confidence: 99%
“…But whether oseltamivir can improve the prognosis of patients needs further study to con rm. Previous studies have shown the potential effect of ribavirin on nCoV [13]. Among the possible studies that should be completed are drug combinations that use the widely available abidol, interferon.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Many of these have been evaluated against SARS-CoV-2 in vitro. These include some medications commonly used for decades, such as chloroquine, [11][12][13] arbidol, 14 ribavirin, [15][16][17] lopinavir, etc., [18][19][20] The list also contains some drugs in development, for instance, remdesivir, 11,17 a previously studied drug candidate for treating Ebola infection. [21][22] Among the most notable and also controversial repurposed drugs are chloroquine (CQ) and hydroxychloroquine (HCQ) as shown in Figure 1A, with several initial promising results especially when combined with azithromycin or zinc supplement being reported, [23][24][25][26][27][28][29][30][31] only to be followed by contradicting reports [32][33][34][35][36][37] on lack of efficacy and presence of severe side effects, especially among the higher dosed patients.…”
Section: Introductionmentioning
confidence: 99%